The need for an international investment consensus-building process - Karl P. Sauvant; Federico Ortino (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
As discussions intensify to improve the international investment regime, it would be desirable to initiate an independent, open-minded, multi-stakeholder international investment consensus-building process to examine the range of issues associated with international investment law, to determine systematically what the concerns are, to discuss how and where to address them, and to propose solutions.
Keywords: 330